37 Neutrophil to lymphocyte ratio as a predictor of outcomes and plaque burden in ST segment elevation myocardial infraction (STEMI). (28th September 2016) - Bajrangee, A; Mahabir, S; Tierney, A; Flood, R; Coughlan, JJ; Hickie, C; Murray, FA; Gorna, B; Srinivas, P; Ullah, I; Sullivan, V; Maree, AO
Abstract : Aim: Several inflammatory markers have been implicated in the pathogenesis of STEMI. The prognostic role of a simple bedside marker like neutrophil to lymphocyte ratio in predicting outcomes after STEMI remains undefined. Methods: Consecutive admissions with STEMI were compared to consecutive patients presenting with stable angina over a 60-day period to St James's Hospital, Dublin. Data gathered included demographics, neutrophil: lymphocyte ratio (NLR) pre angiography, plaque burden using GENSINI and Syntax scores, major adverse cardiac events (MACE) at six week, TIMI grade at end of procedure and ejection fraction at six weeks. Patients with acute sepsis, recent surgery, autoimmune diseases or underlying malignancy were excluded. Results: Ninety-seven patients, 44 with stable angina and 53 with STEMI were followed to six weeks post discharge. Table 1 illustrates the baseline demographics and outcomes. STEMI patients were younger, more likely to have a higher NLR, higher plaque burden, troponin and lower ejection fraction. On multivariate analysis predictors of MACE at six weeks in the STEMI cohort were NLR > 4.5 (OR 1.2, CI: 1–1.34, P = 0.05) but not GENSINI score, Syntax score, ejection fraction or TIMI grade at end of procedure. NLR was not associated with six week MACE in the stable angina cohort. In both groups NLR did not correlate with overall plaque burden. Conclusion: NLR of greater than 4.5 was a predictor of MACE at six weeks in STEMI patients. This inexpensive and widely available marker may be incorporated into standard models of risk prediction in STEMI.